Circulating Vitamin D, Supplement Use, and Cardiovascular Disease Risk: The MrOS Sleep Study - Bajaj, Archna (Endocrine Society, 2014)
CONTEXT: Evidence suggests an inverse association between circulating 25(OH) vitamin D and cardiovascular disease (CVD). OBJECTIVE: To determine the association between serum 25(OH) vitamin D and risk for CVD events. SETTING AND DESIGN: From March 2000 to April 2002, participants were recruited for the Osteoporotic Fractures in Men (MrOS) study. Between December 2003 and March 2005, members of the MrOS cohort were invited to participate in the MrOS Sleep Study. Participants were recruited from 6 clinical centers across the United States and followed for a mean of 5.9 years. Three-thousand-one-hundred-thirty-five men ages 65 and older were included from the MrOS cohort, of whom 116 were excluded for missing vitamin D or CVD data. Participants were divided into two groups based on serum 25(OH) vitamin D levels, <20 ng/mL and ≥20 ng/mL. Participants were followed for CVD endpoints including coronary heart disease (CHD) and cerebrovascular events. Age- and multivariable-adjusted hazard ratios were calculated and stratified by use of vitamin D containing supplements. RESULTS: We observed no significant association between circulating 25(OH) vitamin D and risk of CVD event (HR, 0.91; 95% confidence interval (CI), 0.73–1.13) and CHD event (HR, 0.81; 95% CI, 0.61–1.07). For cerebrovascular events, men with vitamin D deficiency exhibited a higher risk (HR, 1.44; 95% CI, 1.00–2.08) using the minimally adjusted model and after excluding supplement users (HR, 1.70; 95% CI, 1.02–2.83). CONCLUSIONS: 25(OH) vitamin D was not associated with risk of CVD and CHD events. However, vitamin D deficiency may be associated with an increased risk of cerebrovascular events.